On the number of eigenvalues of Schrödinger operators with complex potentials - Frank,RL; Laptev,A; Safronov,O (Journal of the London Mathematical Society, 2016)
We study the eigenvalues of Schrödinger operators with complex potentials in odd space dimensions. We obtain bounds on the total number of eigenvalues in the case where VV decays exponentially at infinity.